Simulation study on parameters of steam turbine governing system based on power grid stability analysis. (September 2020) - Wen, Libin
Abstract: Limited to the general software model of power grid stability analysis can not be changed and added, the parameter setting of steam turbine regulating system is improper, and it will be difficult to model and simulate if it does not conform to the relevant software model; moreover, improper parameter setting of steam turbine regulating system will also cause large fluctuation of generator output power in the process of unit primary frequency regulation, which will affect the stable operation of power grid. In this paper, through the simulation analysis and experimental research of the turbine governing system, the relevant control parameters are changed and optimized, so that the actual unit governing system model is consistent with the general calculation software model of power grid stability, so as to meet the technical requirements of power grid stability analysis and generator unit access to the grid; at the same time, the stability and rapidity of the unit participation in power grid primary frequency regulation are improved.